Effectiveness of combined interventions focused on smoking cessation in patients with schizophrenia: a systematic review - Sofia Sá Almeida Pinho (2021)
Background: Smoking is a significant risk factor for mortality and morbidity among patients with schizophrenia. Objective: To clarify the effectiveness of multimodal smoking cessation interventions in adult smokers diagnosed with schizophrenia. Methods: A systematic review was conducted according to PRISMA guidelines. Relevant electronic databases were searched for clinical trials that combined pharmacological and non-pharmacological smoking cessation interventions for patients with schizophrenia, published up to October, 2020. Primary outcomes were smoking abstinence and smoking reduction. Secondary outcomes consisted in psychiatric symptoms. Results: A final sample of nine articles was obtained from a total of 208 studies. All studies reported higher biochemically validated smoking reduction rates after treatment. However, the majority of the studies reported low smoking abstinence rates, which progressively decreased over time. Multimodal interventions did not worsen psychiatric symptoms. Conclusion: Evidence suggests that multimodal smoking cessation interventions for individuals diagnosed with schizophrenia should be recommended by clinicians, as they showed to be effective in reducing smoking without worsening psychiatric symptoms. Further studies are needed to understand how interventions can become more effective in helping patients achieve long-term smoking abstinence.